Efectos de la sentencia C-035 de 2016 en los contratos de concesión minera en zonas de páramo (2018)
This work intends to analize the legal protection of páramo ecosystem and its incidence in the contracts of mining concession. Thus, it proposes that the prohibition emanating from judgment C035 of 2016, leads to the declaration of nullity of the contract for an unlawful object and therefore to the incapacity to execute it. Furthermore, it studies each of the possible scenarios in which the mining concession contract can be found in order to analyze the State responsibility according to the specific circumstances of each case.